Diurnal and seasonal variations of radon (222Rn) and their dependence on soil moisture and vertical stability of the lower atmosphere at Pune, India. (15th November 2019) - Victor, N. Jeni; Siingh, Devendraa; Singh, R.P.; Singh, Rejesh; Kamra, A.K.
Abstract: Continuous measurements of the concentration of Radon ( 222 Rn) and its progenies were made with a Radon detector, RTM 2200, at a tropical site, Pune (18° 31′ N, 73° 55′ E, 560 m), India from January to December 2012. Simultaneous measurements of small ions of <1.6 nm diameter were made with a Neutral Air Ion Spectrometer (NAIS). Annually - averaged diurnal variation curves of 222 Rn concentration showed a peak ( 9.9 Bq m −3 ) at 0800 Local Time (LT) and a minimum ( 5.4 Bq m −3 ) at 1800 LT. Diurnal variations of 222 Rn concentration during winter, post-monsoon, and pre-monsoon seasons were almost similar in shape but with decreasing amplitudes in these seasons. However, during monsoon season, 222 Rn concentration was the lowest and remained almost constant throughout the day. Monthly mean value of 222 Rn concentration was the highest in December and the lowest in June. Polonium ( 218 Po) concentration did not show any systematic diurnal variation. Results are explained in terms of surface meteorology, soil moisture, soil temperature, vertical wind velocity, local topography and development of atmospheric boundary layer. 222 Rn concentration increased with soil moisture content of <16%, rapidly dropped down to dry soil values and then remained almost constant with increasing soil moisture. On the other hand, 222 Rn concentration decreased with the increase of upward vertical wind velocity in the atmospheric boundary layer. The diurnal variations of ionization rate, directly estimated from 222 Rn measurements, and calculated from ion concentration measurements showed some similarities but differed in their amplitudes. Annual effective dose of 222 Rn ( 0.075 mSv) as estimated from our measurements at Pune was found below the value prescribed by World Health Organization. Highlights: 222 Rn concentration is the highest in winter and lowest in monsoon season. 222 Rn concentration increases if soil moisture <16% and is constant if > 16%. Annual effective dose (0.075 mSv) is below the limit prescribed by WHO. 222 Rn concentration decreases as vertical wind velocity develops.